Analyzing the use of internet of things (IoT) in artificial intelligence and its impact on business environment. (2022) - Vemuri, Veena Prasad; Priya,; Naik, V. Ramesh; Chaudhary, Vijesh; RameshBabu, K.; Mengstie, Mesay
Abstract: IoT is a network of devices that emerge with connectivity, software, and exchange data. Performing on the internet is constantly converting from the "Internet of computers (IoC)" to the "Internet of things (IoT)". Especially in the business world, the adoption of IoT is becoming highly required in order to protect data and resources. In the case of coming and collecting multiple essential data makes the device difficult to store them, so in that scenario, IoT Device is considered as effective. As IoT is capable of sharing vital data through a wireless network, the data remains safe and protected. All the processes of business and its development underlying the procedure of data exchange along with gathering. In this scenario, IoT has the ability to handle the data and record the pattern of the business process. In addition, customer interaction with the devices also can be managed by the IoT network. The business process can be effectively preceded with the help of IoT technology. In the business process, better information with high quality, productivity can be balanced in order to draw the attention of the consumers with this advanced technology system. IoT devices have many benefits, which can improve the business value, and it is described in the discussion part of the research work. In this study, primary along with secondary data analysis have been conducted based on a thematic approach and in that regard, four themes have been prepared and discussed in accordance with different research objectives. The study concluded about the business development by using IoT devices and highlighted the future scope of the research. Here, in this research, the descriptive method was applied to analyze the primary and secondary data. Thematic analysis of the data has become beneficial in getting the best understanding of the topic. Moreover, this study will be helpful for business leaders to understand both the positive and negative approaches of this network system.